Daniel Templon : dix ans. - Millet, Catherine (Paris : Galerie Daniel Templon, 1978)
Arman ; Beckley, Bill ; Ben ; Bioules, Vincent ; Cane, Louis ; Flavin, Dan ; Judd, Don ; Kelly, Ellsworth ; De Kooning, Willem ; Le Gac, Jean ; Mosset, Olivier ; Motherwell, Robert ; Noland, Kenneth ; Olitski, Jules ; Poons, Larry ; Ripps, Rodney ; Serra, Richard ; Shields, Alan ; Stella, Frank ; Thiolat, Dominique ; Venet, Bernar ; Warhol, Andy
Daniel Templon : dix ans, Daniel Templon, Paris, 7 octobre - 16 novembre 1978
boek